Possible association between polycythemia and half and half nails. Issue 5 (2nd July 2020) - Kado, Soichiro; Kamiya, Koji; Maekawa, Takeo; Komine, Mayumi; Murata, Satoru; Ohtsuki, Mamitaro
Abstract : Half and half nail is a type of pseudoleukonychia characterized by proximal whitish areas that are sharply demarcated from red, pink, or brown areas distally on the nail bed. It often occurs in patients with chronic renal disease. Although cases of half and half nails with other diseases have been reported, the exact cause remains unclear. This is the first case report describing the possible association between polycythemia and half and half nails.